Reconnecting Religion and Community in a Small City: How Urban Amenities Afford Religious Amenities - Dugandzic, Audra (Sociology of religion, 2022)
Recently, sociologists of religion have argued that rather than treating geographical location as a mere backdrop against which religion happens, scholars ought to theorize how place characteristics influence, and are shaped by, religion. In particular, they focus on urbanicity, a key variable in the secularization debate. Drawing on interviews with 50 Catholic and non-Catholic residents of a small city just outside of Washington, D.C. along with participant observation data, I argue that one way to examine how urbanicity—and space and place more generally—matters for religion is to identify its affordances, or features of an environment that allow for certain lines of action. Specifically, I show how urban amenities can afford the creation of religious amenities that support religious practice. I also demonstrate how the concepts of affordances and amenities can be used to theorize place characteristics, and their relationship with religion, more systematically.